31‐4L: Late‐News Paper: Challenges and Progress of Small Bending Radius Foldable AMOLED Display Module Technology. Issue 1 (May 2017) - Lin, Li; Dang, Pengle; Hu, Kun; Gao, Xiaoyu; Huang, Xiuqi
Abstract : AMOLED on plastic substrates is expected to be the best candidate for foldable display. However, for small bending radius foldable AMOLED display modules, researches on module process and stress resistance material still remain essential and challenging. In this paper, recent work on a 7 inch full‐function foldable AMOLED display module is introduced. In addition, the failure modes after 100k times folding cycle under bending radius less than 3mm are also discussed.